Abnormal Resting Brain Activity in Patients With Functional Dyspepsia Is Related to Symptom Severity - Zeng, Fang; Qin, Wei; Liang, Fanrong; Liu, Jixin; Tang, Yong; Liu, Xuguang; Yuan, Kai; Yu, Shuguang; Song, Wenzhong; Liu, Mailan; Lan, Lei; Gao, Xin; et al. (Gastroenterology (New York, N.Y. 1943), 2011)
Abnormal processing of visceral sensation at the level of the central nervous system is believed to be involved in functional dyspepsia. However, compared with studies of stimulation-related changes in brain activity, few studies have focused on resting brain activity, which also is important in pathogenesis. We mapped changes in resting brain glucometabolism of patients with functional dyspepsia, compared with healthy subjects, and attempted to correlate abnormal brain activity with symptom severity. We performed fluorodeoxyglucose positron emission tomography–computed tomography on 40 patients with functional dyspepsia and 20 healthy subjects who were in resting states. The symptom index of dyspepsia and the Nepean dyspepsia index were used to determine symptom severity. The positron emission tomography–computed tomography data were analyzed using statistical parametric mapping software. Compared with healthy subjects, patients with functional dyspepsia had higher levels of glycometabolism in the bilateral insula, anterior cingulate cortex (ACC), middle cingulate cortex (MCC), cerebellum, thalamus, prefrontal cortex, precentral gyrus, postcentral gyrus, middle temporal gyrus, superior temporal gyrus, putamen, right parahippocampal gyrus, claustrum, and left precuneus ( P < .001). The signal increase in the ACC, insula, thalamus, MCC, and cerebellum was correlated with symptom index of dyspepsia scores and Nepean dyspepsia index scores ( P < .01). The glycometabolism in ACC, insula, thalamus, MCC, and cerebellum of patients with more severe functional dyspepsia was significantly higher than that of patients with less severe functional dyspepsia ( P < .005). In patients with functional dyspepsia, resting cerebral glycometabolism differs significantly from that of healthy subjects. The ACC, insula, thalamus, MCC, and cerebellum might be the key regions that determine the severity of symptoms.